Mathematical Literacy Ability and Critical Thinking Significantly Influence A Person’s Effectiveness In Solving Mathematical Problems - Sulistyanti, Erin Zahra; Sofyan, Rindu Asmarani; W, Wahyunengsih (Madani: Jurnal Ilmiah Multidisiplin, 2025)
The objective of this research endeavor is to ascertain the extent to which an individual's capacity for critical thinking and mathematical literacy influences their efficacy in addressing mathematical problems The study employs a document analysis strategy, systematically reviewing and synthesizing current scholarly literature to find patterns and indicators that connect mathematical literacy and critical thinking to effective problem-solving. The study looks at how common these indicators are across different academic journals and publications, to figure out if critical thinking and mathematical literacy are generally accepted as important elements in effective mathematical problem-solving. According to the data, the vast majority of the literature that was assessed specifically includes mathematical literacy and critical thinking as important factors affecting the results of problem-solving. In particular, the data demonstrates that more journals and publications favor including these indicators than do not. This indicates a substantial consensus among scholars that critical thinking, characterized by analytical reasoning, evaluation, and synthesis, alongside mathematical literacy, which is delineated as the capability to understand, apply, and interpret mathematical concepts in diverse contexts, are both crucial for effective resolution of mathematical problems. This analytical discourse underscores the imperative to integrate mathematical literacy alongside critical thinking competencies within educational paradigms to enhance students' proficiency in problem-solving. By delivering empirically grounded evaluations that possess the capacity to shape curriculum innovation, instructional methodologies, and assessment strategies tailored to promote these critical skills, the research contributes significantly to the existing dialogue concerning mathematics pedagogy